ĐÁNH GIÁ KẾT QUẢ XA ĐIỀU TRỊ BẢO TỒN GÃY KÍN TRÊN LỒI CẦU XƯƠNG CÁNH TAY Ở TRẺ EM TẠI BỆNH VIỆN HỮU NGHỊ VIỆT ĐỨC (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the long-term results of closed supracondylar humeral fracture treatment in children using reduction and casting at Viet Duc Friendship Hospital from January 2023 to January 2025.Subjects and methods: A retrospective descriptive cross-sectional study was conducted on 274 children with supracondylar humeral fractures treated conservatively at Viet Duc Friendship Hospital from January 2023 to January 2025.Results: The most common age group was 6-10 years old, with boys more frequently affected than girls at a ratio of 2/1. The most common Gartland grade was grades II-III, accounting for 77%. All children with grade 3 callus were followed up for a minimum of 10 months. After treatment, the results were very good (41.1%), good (45.3%), average (11.7%), and poor (2.9%). The most common sequela after stable treatment was trigeminal elbow, accounting for 20.4%.Conclusion: This method is effective, easy to perform, and is the preferred and safe option for treating supracondylar humeral fractures in children.
Keywords: long-term results of supracondylar humeral fractures in children, conservative treatment.